Characterization of Acid-Treated Carbon from Snapper (Lutjanidae) and Red Grouper (Epinephelus spp.) Bones Using HCl and H3PO4 - Juliana, Mia; Dewi, Desak Ayu Sista (Jurnal Teknologi dan Industri Pangan, 2026)
Fish processors usually discard fish bones as waste. The transformation of fish bones into carbon materials presents promising feasibility in view of sustainability. Acid-treated carbon is an inexpensive chemical adsorption material whose behavior is strongly related to its structural and compositional features. This work produced and characterized carbon materials from fish bone waste modified by H3PO4 and HCl. Snapper and red grouper (RG) fish bones were the raw materials. Heads of RG constituted 46.6% of the total weight, which is significantly higher than the 25.1% of snapper. While the bone and head of RG reached 18.11 and 17.38%, respectively, the snapper fish produced a higher percentage of 30% variability in nitrogen. The yield for acid treatment with H3PO4 was relatively higher (140%) than that of HCl (126.7%). The H3PO4-treated carbon showed FTIR peaks at 3646.58, 2989.79, 2348.43, and 1491.04 cm-1, while the HCl-treated carbon produced peaks around 3630.19, 2340.72, 1318.4, 1058, and 659.68 cm-1. The EDS analysis provided more carbon in HCl-treated samples (52.26%) than in H3PO4 (44.12%). The results provide initial compositional and structural analysis of acid-treated fish bone carbon. However, researchers should justify their practicability through additional experiments (e.g., BET surface area and adsorption performance tests) in the adsorption or water treatment fields.